Psychometric evaluation of a questionnaire to evaluate organizational capacity development for faculty development programs - Mahla Salajegheh; John Sandars; Ali Norouzi; Azim Mirzazadeh; Roghayeh Gandomkar (Wolters Kluwer Medknow Publications, 2020)
Background: Organizational capacity development is an important outcome of faculty development programs, but there is a lack of an appropriate instrument for its evaluation. Aims and Objectives: The aim of this study was to develop a questionnaire to evaluate the organizational capacity development for faculty development programs and to test its psychometrics. Materials and Methods: The initial capacity development for faculty development questionnaire (CDQ-FD) of 26 items was developed based on a literature review and opinion of experts. Content validity ratio (CVR), content validity index (CVI), content validity index for items (I-CVI), and the content validity index for scales (S-CVI) were computed for content validity. Confirmatory factor analysis (CFA) and exploratory factor analysis (EFA) were performed for construct validation. Results: The score for CVR, CVI, I-CVI, and S-CVI was 0.71, 0.83, 0.87, and 0.90, respectively. EFA resulted in a three-factor model with total variance extraction of 64%. Cronbach's alpha and Spearman Brown coefficient were investigated for reliability assessment. The Cronbach's alpha of overall scale was 0.8 and the test-retest reliability of the overall scale was 0.78. The final CDQ-FD contained 21 items and three categories. Conclusions: The CDQ-FD questionnaire appears to be a valid and reliable instrument for the evaluation of organizational capacity development for faculty development in the medical education.